Bose-Einstein condensation in real space - Valencia, J.J.; de Llano, M.; Solís, M.A. (Revista Mexicana de Física, 2004)
We show how Bose-Einstein condensation (BEC) occurs not only in momentum space but also in coordinate (or real) space. Analogies between the isotherms of a van der Waals classical gas of extended (or finite-diameter) identical atoms and the point (or zero-diameter) particles of an ideal BE gas allow concluding that, in contrast with the classical case, the volume per particle vanishes in the pure BE condensate phase precisely because the boson diameters are zero. Thus a BE condensate forms in real space without exhibiting a liquid branch as does the classical gas.